Divisive or objective the law about choosing the principals of the school units (4327/2015)? Study case in prefecture of Thessaloniki - Αργυροπούλου Ελευθερία; Φιλίππου Δημήτριος (Education Sciences, 2018)
The current article moves in two basic thematic pivots: a) the nature and the characteristics of the collision as a specialized phenomenon as part of the school unit of the secondary education and b) the collisions that came up in the school units of the secondary education due to the introduction of the procedure of choosing the principals from the teachers’ board of the school unit. The theoretical substantiation of the two pivots was carried out with the assistance of bibliography and the article writing from the Greek and foreign reality. The survey of the second part of the article was limited in the study of the desiderata in schools of Thessaloniki (study of the Case)